An unexpected event after deep vein thrombosis in spinal cord injury: Ruptured Baker's cyst. (4th March 2022) - Mengi, Alper; Ilhan, Ipek
Abstract : Context: Deep vein thrombosis (DVT) is a well-known complication of spinal cord injury (SCI). Low-molecular-weight heparin (LMWH) may be used in SCI patients who develop DVT, but can lead to subcutaneous bleeding. If subcutaneous bleeding occurs, then lymphedema, cellulitis, muscle or tendon tearing, or baker's cyst rupture should be considered in the differential diagnosis. Findings: Herein, we present a 61-year-old female patient who was hospitalized for rehabilitation due to paraplegia, and used LMWH due to DVT development. The patient suddenly developed pain, swelling, and discoloration of the left lower extremity. Although subcutaneous hemorrhage was considered initially, ultrasound and MRI revealed a ruptured Baker's cyst. In addition to supportive therapy, ultrasound-guided aspiration was performed. Conclusion/Clinical Relevance: In this report, we present a case of clinically severe Baker's cyst rupture, which occurred in the lower extremity of a SCI patient using LMWH due to DVT in the same extremity. To our knowledge, no similar cases have been reported.